2012
DOI: 10.1186/1757-1146-5-23
|View full text |Cite
|
Sign up to set email alerts
|

Foot health education for people with rheumatoid arthritis — some patient perspectives

Abstract: BackgroundPatient education is an important component of foot health management for people with rheumatoid arthritis (RA). The content and strategies for delivery require investigation in relation to the patients’ needs. This study explores patients’ experiences of foot health education, to inform how the patients’ needs could be identified in clinical practice and inform effective education delivery.MethodA focus group was used to collect data. The dialogue was recorded digitally, transcribed verbatim and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 51 publications
(61 reference statements)
6
21
0
Order By: Relevance
“…These can be achieved with early access to foot health assessment, and management which includes foot orthoses, therapeutic footwear (Arthritis and Rheumatism Musculoskeletal Alliance, ; National Institute for Clinical Excellence, ), and the care of nail and skin problems, together with patient education on how to contribute to this management (Williams et al, ). As patient education for people with RA has a positive effect in relation to their general disease management and overall health (Albano et al, ; Fautrel et al, ), foot health education (FHE) is also recognized as being essential (Graham et al, 2012a,b, Podiatric Rheumatic Care Association, ; Williams et al, ). Figure outlines the general aspects of foot health that healthcare professionals should aim to provide, depending on the needs of the person with RA and based on current guidelines (North West Podiatry Clinical Effectiveness Group, ).…”
Section: Introductionmentioning
confidence: 99%
“…These can be achieved with early access to foot health assessment, and management which includes foot orthoses, therapeutic footwear (Arthritis and Rheumatism Musculoskeletal Alliance, ; National Institute for Clinical Excellence, ), and the care of nail and skin problems, together with patient education on how to contribute to this management (Williams et al, ). As patient education for people with RA has a positive effect in relation to their general disease management and overall health (Albano et al, ; Fautrel et al, ), foot health education (FHE) is also recognized as being essential (Graham et al, 2012a,b, Podiatric Rheumatic Care Association, ; Williams et al, ). Figure outlines the general aspects of foot health that healthcare professionals should aim to provide, depending on the needs of the person with RA and based on current guidelines (North West Podiatry Clinical Effectiveness Group, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the practice of tailoring advice as opposed to adhering to a standard message has been associated with increases in physical activity levels in the short-term [35], so such tailoring may be desirable. The tailoring of advice to the patient has also been advocated in diabetic education [39,40] and foot health education for patients with rheumatoid arthritis [41].…”
Section: Discussionmentioning
confidence: 99%
“…Negotiations with the patient on balancing the risks and benefits of an intervention will be greatly affected by the patient' s priorities for treatment. Patients' perceptions / knowledge and expectations in relation to their presenting symptoms also need to be ascertained in order to create appropriate dialogue and understanding and engagement with interventions and advice (Graham et al 2012a(Graham et al , 2012b.…”
Section: Disease-modifying Agentsmentioning
confidence: 99%
“…Lorig et al (2005) and Kjeken et al (2006) demonstrated that people with RA who are actively involved in their disease management have better outcomes, improved self-efficacy, less pain and reduced incidence of depression. In relation to foot problems, it has been recommended that patientcentred education should be provided to enable patients to make informed choices about their footcare (Graham et al 2012a(Graham et al , 2012bWilliams et al 2011).…”
Section: Lifestyle and Education Strategiesmentioning
confidence: 99%
See 1 more Smart Citation